17(-19-8f)=

Simple and best practice solution for 17(-19-8f)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17(-19-8f)= equation:


Simplifying
17(-19 + -8f) = 0
(-19 * 17 + -8f * 17) = 0
(-323 + -136f) = 0

Solving
-323 + -136f = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '323' to each side of the equation.
-323 + 323 + -136f = 0 + 323

Combine like terms: -323 + 323 = 0
0 + -136f = 0 + 323
-136f = 0 + 323

Combine like terms: 0 + 323 = 323
-136f = 323

Divide each side by '-136'.
f = -2.375

Simplifying
f = -2.375

See similar equations:

| -p+8/3=p-7/2 | | 14x^2y+16xy-24y= | | 2/3h=14 | | 14x^2y+17xy-24y= | | 4(5+x)=x+15 | | 5x+9=9+7x | | 10x+x=2x+13 | | 55y=18(3y+23) | | 3x+5x-2= | | (0.01)^-3/2 | | 4x+8y+9(-4x)= | | -6x-38=22 | | 7x+8=x+38 | | -8(16x+2)-19= | | -8n+8n=3-n | | 10x^5-31x^4+15x^3= | | 20-(60/(-2*30)-8)*4 | | 5=y | | 10+6x=3x+34 | | 8+5x-2=-14 | | 8x=4+2x | | 14(-11s-19)= | | 1/2x+6=22 | | 5x-4x+x-5+3x= | | 5x^2+15x-54=0 | | 10+.10x=35x | | 7+5x+3x=7 | | 2*-7+4= | | -16(10-5z)+7z= | | 6w-8w=-10 | | -3x^2-5x=-2 | | 2(1-2z)-2(6z+3)=z-6 |

Equations solver categories